Efektivitas Rempah dan Herbal sebagai Antioksidan Alami dalam Pengawetan Ikan Tuna (Thunnus sp.) dan Ikan Nila (Oreochromis niloticus): Meningkatkan Keamanan Mikroba dan Daya Simpan - Hani Widhianata; Arinda Eka Lidiastuti (Jurnal Penelitian Pendidikan IPA, 2025)
Fish is a protein-rich and highly nutritious food. Natural herbs and spices contain antioxidant and antibacterial compounds that may enhance microbiological safety and extend shelf life. This study aimed to evaluate natural herb and spice-based processing methods for preserving tuna (Thunnus sp.) and nile tilapia (Oreochromis niloticus), along with the effectiveness of specific spices in reducing oxidation and microbiological contamination. Two marination approaches were applied, using both uncooked and cooked spice mixtures. Three recipes were prepared, recipe 1: garlic, pepper, salt, turmeric, coriander, lemongrass, recipe 2: garlic, pepper, salt, rosemary, oregano, thyme, lemon and recipe 3: garlic, pepper, salt, coriander, lemongrass, chili pepper, curry leaves, asam sunti. Unmarinated fish served as the control. All samples were vacuum-packed in retort pouches and stored at 1-4 °C for 1 h, 3, 5, and 7 days. Microbial analysis included total aerobic bacteria, Escherichia coli, Coliforms, Salmonella spp., Shigella spp., yeast and mold. Marination with herbs and spices significantly reduced microbial contamination compared to the control. The combined use of herbs and spices effectively improved microbial safety and extended the shelf life of tuna and nile tilapia. These findings support the application of herbs and spices as natural preservation agents in fish products, offering a safer and more sustainable alternative in fish preservation.